2018
DOI: 10.1111/ceo.13424
|View full text |Cite
|
Sign up to set email alerts
|

Two different initial treatment regimens of ranibizumab in myopic choroidal neovascularization: 12‐month results from a randomized controlled study

Abstract: Importance:The optimal treatment regimen for myopic choroidal neovascularization (mCNV) is essential to understand but currently poorly studied. Background: To date, there is still no consensus on the optimal dosage and frequency of anti-vascular endothelial growth factor injections in treating mCNV. Design: A prospective, single-centre, single-blind, randomized controlled study. Participants: Adult patients with active mCNV. Methods: Patients were randomized 1:1 to one or three doses initial ranibizumab treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…All investigations followed the tenets of the Declaration of Helsinki. A total of 57 eyes of 57 patients with active unilateral mCNV were enrolled in this study from March 2014 to July 2018, including 20 patients who participated in a previous published study (SMILE: a single blind clinical trial “Treatment and assessment Strategy for MyopIc CNV with LucEntis: a single-center, prospective randomized controlled study,” NCT03042871) ( 14 ). The inclusion criteria were as follows: (1) unilateral active subfoveal or juxtafoveal CNV associated with high myopia (spherical equivalence < −6.0 D or axial length > 26 mm) confirmed by fundus fluorescein angiography (FFA) with a hyperfluorescent CNV network on early frames and leakage on late frames; (2) patients with baseline best-corrected visual acuity (BCVA) in the affected eye from 24 to 73 ETDRS letters; and (3) patients who received 3+prn (pro re neta) intravitreal ranibizumab treatments for 12 months.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All investigations followed the tenets of the Declaration of Helsinki. A total of 57 eyes of 57 patients with active unilateral mCNV were enrolled in this study from March 2014 to July 2018, including 20 patients who participated in a previous published study (SMILE: a single blind clinical trial “Treatment and assessment Strategy for MyopIc CNV with LucEntis: a single-center, prospective randomized controlled study,” NCT03042871) ( 14 ). The inclusion criteria were as follows: (1) unilateral active subfoveal or juxtafoveal CNV associated with high myopia (spherical equivalence < −6.0 D or axial length > 26 mm) confirmed by fundus fluorescein angiography (FFA) with a hyperfluorescent CNV network on early frames and leakage on late frames; (2) patients with baseline best-corrected visual acuity (BCVA) in the affected eye from 24 to 73 ETDRS letters; and (3) patients who received 3+prn (pro re neta) intravitreal ranibizumab treatments for 12 months.…”
Section: Methodsmentioning
confidence: 99%
“…In patients with mCNV, VA improved about 13–15 Early Treatment Diabetic Retinopathy Study (ETDRS) letters 1 year after a scheduled anti-VEGF treatment ( 7 , 8 , 14 ). Without treatment, VA may drop to 20/200 or worse within 5 years in patients with mCNV ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…These features may lead to treatment requirements that are different from those that have become established for neovascular age‐related macular degeneration (nAMD) in Caucasians and also to different outcomes. The SMILE study (Treatment and assessment Strategy for MyopIc CNV with LucEntis) by Li et al of Clinical and Experimental Ophthalmology provides useful evidence to address this gap in knowledge …”
mentioning
confidence: 99%
“…There was no consensus prior to the study by Li et al on whether treatment of mCNV should start with three consecutive monthly loading doses or one single initial dose. A non‐randomized prospective trial reported that bevacizumab with one initial treatment, followed by prn, achieved the same visual and anatomical outcomes with fewer injections but had a higher rate of recurrences, similar to treatment with 3‐monthly loading injections followed by prn .…”
mentioning
confidence: 99%
See 1 more Smart Citation